The choice factory : how 25 behavioural biases influence the products we decide to buy - Shotton, Richard (Hampshire, Great Britain : Harriman House Ltd, 2018)
Before you can influence decisions, you need to understand what drives them. In The Choice Factory, Richard Shotton sets out to help you learn. By observing a typical day of decision-making, from trivial food choices to significant work-place moves, he investigates how our behavior is shaped by psychological shortcuts. With a clear focus on the marketing potential of knowing what makes us tick, Shotton has drawn on evidence from academia, real-life ad campaigns and his own original research. The Choice Factory is written in an entertaining and highly-accessible format, with 25 short chapters, each addressing a cognitive bias and outlining simple ways to apply it to your own marketing challenges. Supporting his discussion, Shotton adds insights from new interviews with some of the smartest thinkers in advertising, including Rory Sutherland, Lucy Jameson and Mark Earls. From priming to the pratfall effect, charm pricing to the curse of knowledge, the science of behavioral economics has never been easier to apply to marketing. The Choice Factory is the new advertising essential.
The 25 biases. The fundamental attribution error -- Social proof -- Negative social proof -- Distinctiveness -- Habit -- The pain of payment -- The danger of claimed data -- Mood -- Price relativity -- Primacy effect -- Expectancy theory -- Confirmation bias -- Overconfidence -- Wishful seeing -- Media context -- The curse of knowledge -- Goodhart's law -- The Pratfall effect -- Winner's curse -- The power of the group -- Veblen goods -- The replicability crisis -- Variability -- Cocktail party effect -- Scarcity -- Ethics -- Conclusion.
Includes bibliographical references and index.
Keywords: Consumer behavior; Influence (Psychology); Consumers -- Attitudes; Bibliography B3 FLM - Marketing Strategies & Tactics